Using Lean Manufacturing Techniques to Improve Production Efficiency in the Ready Wear Industry and a Case Study - (:unkn) unknown (INST CHEMICAL FIBRES, 2013)
Businesses apply different techniques to keep pace with the incremental competition conditions and changing consumer demands. Lean manufacturing is one of the most effective techniques, which is a systematic approach to identifying and eliminating waste through continuous improvement by flowing the product. The implementation of lean manufacturing starts with the development of Value Stream Maps. A value stream is comprised of all the actions, both value added and,on-value added. The main strategy of lean manufacturing, is increasing the operating speed, reducing the duration of flow quality, and improving the cost and delivery performance. This study was carried out at a men's shirt producer i.e. a ready wear company. First of all, the current state of the production lines was analysed within the scope of the study. Then shirt production lines were organised with the lean manufacturing techniques. As a result, some improvements were made in productivity, quality and lead time.
Keywords: ready wear industry; lean manufacturing men's shirt; productivity; PERFORMANCE; SIMULATION